Polyethersulfone Block Copolymers for Membrane Applications. Issue 20 (18th September 2019) - Weber, Martin; Rajak, Anil; Maletzko, Christian
Abstract: Polyarylethersulfones (polysulfone: PSU, polyethersulfone: PESU) belong to the group of established membrane materials and are mainly used for production of ultra‐ and microfiltration membranes. They offer several advantageous properties like hydrolysis and chemical resistance, mechanical strength and bio‐compatibility. A general drawback of these polymers compared to the more polar membrane materials cellulosetriacetate or polyacrylonitrile is the hydrophobic nature of the polyarylethersulfone which can be quantified by the contact angle versus water. An improved synthetic pathway to segmented block copolymers based on polyarylethersulfones and various aliphatic polyethers is presented as well as the characterization of the obtained block copolymers and their use for membrane preparation. Abstract : To improve the hydrophilicity of polyarylethersulfones (polysulfone: PSU, polyethersulfone: PESU) block copolymers with polyalkyleneoxide units are prepared and characterized. Using different PEO‐PPO‐PEO copolymers as polyalkyleneoxides two phase PESU‐PEO‐PPO‐PEO block copolymers as interesting membrane materials are obtained.